Preparation of carrier-free astaxanthin nanoparticles with improved antioxidant capacity - Yu, Fei; Chen, Jiaxin; Wei, Zizhan; Zhu, Pingchuan; Qing, Qing; Li, Bangda; Chen, Huimin; Lin, Weiying; Yang, Hua; Qi, Zhongquan; Hong, Xuehui; Chen, Xiao Dong (Frontiers in Nutrition, 2022)
Astaxanthin (AST), a red pigment of the carotenoids, has various advantageous biological activities. Nevertheless, the wide application of AST is restricted due to its poor water solubility and highly unsaturated structure. To overcome these limitations, carrier-free astaxanthin nanoparticles (AST-NPs) were fabricated through the anti-solvent precipitation method. The AST-NPs had a small particle size , negative zeta potential and high loading capacity . Analysis of DSC and XRD demonstrated that amorphous AST existed in AST-NPs. In comparison with free AST, AST-NPs demonstrated enhanced stability during storage. Besides, it also showed outstanding stability when exposed to UV light. Furthermore, the antioxidant capacity of AST-NPs was significantly increased. In vitro release study showed that AST-NPs significantly delayed the release of AST in the releasing medium. These findings indicated that AST-NPs would be an ideal formulation for AST, which could contribute to the development of novel functional foods.